2013
DOI: 10.1080/09297049.2013.856395
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the dimensional change card sort and backward digit span by young children with autism without intellectual disability

Abstract: The early development of executive function (EF) and its relation to autism symptom expression is of considerable theoretical interest, particularly in children without general cognitive delay. Executive function was tested in 23 children with autism spectrum disorders (ASD) without intellectual disability and 20 age- and IQ-matched typically developing children. Even though performance was equivalent between the two groups on tests of general intelligence, flexibility in card sorting was lower for children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
3
30
2
3
Order By: Relevance
“…This result is consistent with previous findings [31,32] . Our result might suggest that cognitive flexibility measured by the WCST does not reflect social adaptation in the real world.…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with previous findings [31,32] . Our result might suggest that cognitive flexibility measured by the WCST does not reflect social adaptation in the real world.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, children with ASD exhibit an uneven profile in their EF abilities, with consistent impairments on set‐shifting skills alongside relatively preserved verbal working memory for simple tasks (as demonstrated by Faja & Dawson, in 6‐ to 8‐year‐olds). So far, studies examining EF in ASD have only included monolingual children.…”
Section: Executive Functions In Autism Spectrum Disordersmentioning
confidence: 83%
“…Because IQ contributes to performance on most cognitive tests, including EF (Friedman et al, 2006; Lezak et al, 2013), it is standard in neuropsychological research to control for IQ to ensure that any observed effects can truly be attributed to the specific construct of interest (Eastvold, Suchy, & Strassberg, 2011; Faja & Dawson, 2014). Thus, we used estimated IQ as a covariate in follow-up analyses.…”
Section: Methodsmentioning
confidence: 99%